PENGGUNAAN BOSARANG UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM MENULIS TEKS DESKRIPTIF DI KELAS VIII SMPN 1 SUMARORONG - Yusriati; Syam, Ulfa; Rampeng (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
This research is aimedto know the outcomeof using Puzzle Human (Bosarang) to improvestudents’ writing skill of descriptive text at the eight grade students of SMPN 1 Sumarorong. This research was classified as pre-experimental design to one group class. The population of this research were the eighth-grade students of SMPN 1 Sumarorong in academic year 2020/2021 that consist of 150 students. Purposive sampling technique was used to take a class as the sample of the research which consist of 32 students. The research used inferential analysis of t-test by using SPSS v.16.0, the researcher concludes that the use of puzzle human (Bosarang) can improve students’writing skill of descriptive text. The results of the research showed that there was a significant improvement in the students’ mean score writing skillwhen the students were taught by puzzle human (Bosarang) and whenwere taught only using textbook. The mean score of the students’ writing competence increased from 52,50 in pre-test, to 73,96 in post-test. The significance value calculated 0.000 is smaller than 0.05 (P-value = 0.000 < 0.05). Therefore, the hypothesis of this study was accepted. It shows that Bosarang totally increases students’ skill in writing